Forms and Performances of Collective Agricultural Innovations: The Example of Warrantage System Management in Benin - Machioudou, Samsoudine I.; Moumouni-Moussa, Ismail; Baco, Mohamed Nasser (Journal of Agricultural Studies, 2023)
How to innovate collectively to face common challenges? This study seeks to investigate the performance of collective innovation within warrantage systems in Benin. Employing the "snowball" technique, primary data was gathered from six organizations involved in promoting warrantage systems via semi-structured interviews, which were subsequently analyzed through discourse analysis. The performance of collective innovations was evaluated by means of six focus groups with stakeholders and semi-structured interviews with management committees. Economic efficiency, member interaction, external relations, and sustainability of the system are the performance indicators. The findings revealed three distinct forms of collective innovation: collective innovation based on cognitive proximity, that based on social proximity and that based on organizational proximity. Collective innovation based on organizational proximity demonstrated the most favorable performance. The performance of collective innovation is determined by the actor’s interaction capacity.